DAMPAK MINYAK BUAH MERAH, Pandanus conoideus LAM PADA PERFORMANSI YUWANA KERAPU SUNU, Plectropomus leopardus - Titiek Aslianti; Philip Teguh Imanto; Made Suastika (Universitas Gadjah Mada, 2009)
Market price of coral trout grouper was increasing by the color performance of fish. Beta-carotene diet was proposed to escalate pigmentation of coral trout grouper. Red fruit oil (Pandanus conoideus, Lam) which known as potential beta-carotene source was used in coral trout diets. The dosage of 5, 2.5 and 0 ml were supplemented to the every kilogram of pellet fed as a treatment in this observation during three-month period. Three hundred and fifty juveniles with initial total length 14.28±0.2 cm and 43.41±2.62 g of body weight were stocked in fiberglass tank of 5m³ seawater. Growth data were collected monthly, while color performance was taken by digital photography at the end of observation and analyzed by